(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2023)
In this article, the opinions related to our traditions, such as blessing, wish, thanks, word magic, curses, which are units of thanks and curses that are one of the forms of folklore, and the reflection of the national culture that is preserved during the centuries are given and explained through the examples.